Quiet eye duration and performance outcome in petanque / Yallini Selva, Viswanath Sundar and Amir Arifudeen - Selva, Yallini; Sundar, Viswanath; Arifudeen, Amir (Universiti Teknologi MARA, 2023)
Petanque is a competitive skill sport that is popular in Malaysia. Athletes often must perform in a high-pressure situation during a game. The purpose of the research is to understand the influence of the quiet eye duration on the performance outcome across different difficulties amongst the athletes. Ergoneer Dikablis (v3.55) eye-tracking system was used to collect the quiet eye duration of 8 Malaysian petanque athletes in a field setting at the National Sports Council (MSN), Keramat. The athletes were required to shoot the single ball (SB) and double ball (DB) (right ball only) across five different distances from the starting point alternately. The arrangement of a double ball is more difficult compared to a single ball. Three trials were permitted for each distance. Successful trials were recorded when the targeted ball was displaced from its original position in SB (whole ball) and in DB (ball on the right). A previous study found that athletes with higher levels of expertise and successful performance had longer QE duration. The performance outcome and the quiet eye duration were analysed for normality. The Mann-Whitney U-test and Kruskal-Wallis tests were conducted using SPSS statistical software. From the statistical findings, it was found that irrespective of distance, there is a difference in the quiet eye between a single ball and a double ball. As p=0.846, which is greater than p=0.05, there is no significant difference between distance and quiet eye for a single ball. As p=0.865, which is greater than 0.05, there is no significant difference between the distance and quiet eye for the double ball. In conclusion, the duration of the quiet eye is influenced by the difficulty level of the ball arrangement. The performance outcome was not found to be influenced by the quiet eye.